Bank capital ratios across countries: Why do they vary? - Elijah Brewer; George G. Kaufman; Larry D. Wall (Federal Reserve Bank of Atlanta, 2008)
This paper extends the literature on bank capital structure by modeling capital structure as a function of important public policy and bank regulatory characteristics of the home country, as well as of bank-specific variables, country-level macroeconomic conditions, and country-level financial characteristics. The model is estimated with annual data from 1992 to 2005 for an unbalanced panel of the seventy-eight largest private banks in the world headquartered in twelve industrial countries. The results indicate that bank capital ratios are significantly affected in the hypothesized directions by most of the bank-specific variables. Several of the country characteristic and policy variables are also significant with the predicted sign: Banks maintain higher capital ratios in home countries in which the bank sector is relatively smaller and in countries that practice prompt corrective actions more actively, have more stringent capital requirements, and have more effective corporate governance structures.
Keywords: G21; G29; 330; capital requirements; country public and regulatory policies; large banks; Internationale Bank; Bankenliquidität; Basler Akkord; Eigenkapital; Basler Akkord; Bankrisiko; Vergleich; Industriestaaten